Sensitization to common foods and early vascular aging: associations and the mitigating effects of health behaviors - Ruming Shen; Shuaijie Chen; Zhongxing Zhou; Qiong Su; Xiaoyan Lin; Hongzhuang Wang; Feng Peng; Jinxiu Lin; Dajun Chai (BMC Public Health)
Abstract Background Sensitization to common foods is typically considered clinically irrelevant in individuals without symptomatic food allergies. However, recent studies found an association between IgE specific to the mammalian oligosaccharide galactose-α-1,3-galactose and cardiovascular disease (CVD). The aims of this study are to determine whether common food sensitization is associated with early vascular aging (EVA) and to examine whether healthier lifestyle behaviors modifies the association in individuals without CVD. Methods This was a cross-sectional, population-based study of 2788 American participants aged 30 years or older without cardiovascular disease. Total and specific IgE levels for common foods were measured. EVA was defined based on the 10th percentile of the difference between chronological age (CA) and vascular age (VA). Logistic regression models were employed to assess the associations between food sensitization and EVA, and whether healthy lifestyle modified the association. Poisson regression models, ordinal logistic regression models, and linear regressions were performed as sensitivity analysis. Results Sensitization to at least one food allergen associated with an increased risk of EVA (odds ratio [OR] 1.91 [95% confidence interval (CI), 1.1 to 3.3]). Milk sensitization demonstrated the most robust association (OR 7.18, [95% CI, 2.5 to 20.62]). Additionally, moderate to vigorous activities (MVA) (OR 0.33 [95% CI, 0.11 to 0.97]) and sufficient sleep duration (OR, 0.21 [95% CI, 0.07 to 0.65]) mitigate the association between food sensitization and EVA. Similar results were presented in Poisson regression models, ordinal logistic regression models, and linear regressions. Conclusions The findings that common foods sensitization is independently associated with EVA, and that MVA and adequate sleep duration mitigate the association, have significant public health implications. Further research is needed to elucidate the mechanisms.